A common regulatory language for trade and development. (Trade investment guides ;, 2009)
The publication examines changes in the regulatory landscape in the member States of the United Nations Economic Commission for Europe (UNECE), including the recent trend towards "better regulation", i.e. regulations with a greater focus on desired outcomes and more flexibility. This approach can help remove barriers to trade created by differences in national standards and technical regulations. The current volume brings together contributions and research papers prepared by some of the speakers and participants of the International Forum on "Common Regulatory Language for Global Trade", held in June 2006, as well as by the UNECE secretariat.--Publisher's description